Efektivitas Penggunaan Rubrik Analitik dalam Meningkatkan Objektivitas Penilaian Tes Uraian - Leni Kristiana Wabang; Serni Marwina Almet; Roimanson Panjaitan (Indo Publishing, 2026)
Assessment is an essential component of the learning process because it provides information regarding students' achievement of learning objectives. Essay tests are widely used in education due to their ability to measure higher-order thinking skills and students' capacity to express ideas comprehensively. However, scoring essay tests often involves subjective judgment, which may affect the fairness and accuracy of assessment results. This study aims to analyze the effectiveness of analytic rubrics in improving the objectivity of essay test assessment. The research employed a qualitative library research approach by reviewing various relevant scientific publications. Data were collected from journals, books, and academic articles related to analytic rubrics, assessment objectivity, and essay evaluation. The findings indicate that analytic rubrics contribute to increasing scoring consistency, improving reliability, reducing assessment bias, and enhancing transparency in the evaluation process. Therefore, analytic rubrics can be considered an effective assessment tool for supporting more objective and accountable essay scoring practices.